GROWTH RATES OF THE MASSIVE CORAL Porites lutea EDWARD AND HAIME, ON THE COAST OF BONTANG, EAST KALIMANTAN, INDONESIA - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Growth rates (linear skeletal extension) and the timing of skeletal band formation were measured in eight specimens of the massive coral   Porites lutea at three sites (BK1, BK2, and BK3) and three depths, i.e. 1 m , 3 m, and 5 m in each site.  The sites were located in Bontang Kuala Regency, located about 7.5 km from the fertilizing industry, PT Pupuk Kaltim Tbk, Bontang. Growth rates were measured by using two techniques, i.e. X-radiograph and UV-light. Result of the study indicates that  the timing  of  the high density (HD) and low density (LD)  bands  is synchronous  at  the  three  locations.  A one year growth is characterized by three HD bands, one of which is usually very dense.  Illumination of the coral slabs by UV-light revealed a distinct fluorescent banding pattern on all coral specimens.  The data indicate  that the fluorescent bands are usually associated  with the  high density bands which are accreted during the wet  season period. It is  characterized  by high land  run-off  containing elevated concentrations of fulvic and humic acid compounds, and this apparently occurred almost through out the year. However fluorescent bands were absent from a  number  of density couplets,  known as “stress bands”.  The results suggest that in the present study the linier skeletal  extension rates,  based  on  X-ray  radiographic  techniques, are a  more accurate  measure  of  P. lutea growth  rates  then  fluorescence banding. Comparisons   of   the skeletal extension rates   indicate that the growth rates of P.  lutea are not significantly difference (p > 0.05) either between sites or depths. The average of coral growth rates ranged from 0.8-1.2 cm/year. These are significantly correlated (p < 0.01) with the amount of rainfall.  While the amount of rainfalls is not correlated with urea production of fertilizing industry, P.T.Pupuk Kaltim Tbk, which some of them are loss as dust (a core for water vapour) during process production.